Seletividade fisiológica de inseticidas recomendados no controle de Tuta absoluta (Meirick, 1917) (Lepidoptera: Gelechiidae) para o predador Macrolophus basicornis (Stal, 1860 (Hemiptera: Miridae) - Passos, Luis Clepf (2016)
In order to obtain information that may contribute for integrating the biological and chemical control methods of the tomato leafminer Tuta absoluta (Meyrick, 1917) (Lepidoptera: Gelechiidae), this study evaluated the toxicity of five insecticides (teflubenzuron, abamectin, chlorantraniliprole, chlorfenapyr and cartap hydrochloride) recommended to control Tuta absoluta on the predator Macrolophus basicornis (Stal, 1860) (Hemiptera: Miridae), under the hypothesis that teflubenzuron and chlorantraniliprole are less harmful. Laboratory experiments were conducted to evaluate predator mortality caused by the products, one using an inert substrate and nymphs, and two using tomato leaves (extended laboratory), with predator nymphs and adults. We also evaluated mortality caused by the products under greenhouse conditions (semi-field). Moreover, the persistence of the products to the predator nymphs was also evaluated. In each bioassay, insecticides were classified in toxicity classes according to IOBC. Abamectin was classified as toxic to M. basicornis nymphs and adults in all bioassays. Chlorfenapyr showed lethal effect similar to abamectin, except in the inert substrate bioassay, in which it was considered harmless. Cartap hydrochloride was slightly harmful on inert surface and expanded laboratory for adults, but was harmful to nymphs in extended laboratory and moderately harmful under semi-field conditions. Chlorantraniliprole and teflubenzuron were harmless, except for nymphs in the extended laboratory test, and should be preferred in tomato leafminer pest management programs aiming for the preservation of M. basicornis.